Caste and class in a southern town - Dollard, John 1900-1980 (Garden City, New York Doubleday, Anchor Books, 1957)
Analysis of the effects of long-established patterns of discrimination upon the Negro and white citizens of a single Southern town poses the general problem in the specific terms of social research.
Includes bibliographical references and index.
Keywords: African Americans -- Southern States; African Americans -- Social conditions; Southern States -- Social conditions; Southern States -- Civilization